Water quality index in a section of El Gallinazo stream, Aguachica (Cesar - Colombia)eam, Aguachica (Cesar - Colombia) - Saldaña-Escorcia, Rossember; Rodelo-Soto, Kelly Jhoana; Bermudez-Laiton, Dairo Ivan (Ecosistemas y Recursos Agropecuarios, 2024)
The Water Quality Index (WQI) is perceived as an effective method to fully represent water quality, allowing the collection of information on water resources that does not exist in the area, thus allowing the generation of adequate water management and governance. The objective was to determine the water quality in a section of the El Gallinazo stream using the water quality index. Dissolved oxygen (DO), biological oxygen demand (BOD), turbidity, hydrogen potential (pH), electrical conductivity (EC), temperature change (T°C) and phosphates were quantified. The results of the evaluated parameters were as follows: DO from 39.22 to 83.6% saturation; BOD5 from 1.0 to 60 mg O2 L-1; COD from 1.0 to 240 mg L-1; turbidity from 1.33 NTU to 56.82 NTU; T from 20.3 to 27°C; pH from 5.9 to 7.6; EC from 126.3 to 223 μS/cm; and phosphates from 0.02 to 1.07 mg L-1. The evaluation of the water quality in the upper stretch of the Gallinazo River showed a range of results according to the Water Quality Index (WQI), which varied between 0.42 and 0.53, with an average of 0.47, indicating a low water quality in this area. The pollution present in this section of the river is attributed to the socioeconomic activities (cattle ranching, monoculture and laundry) carried out in the area. Therefore, it is concluded that the water does not meet adequate standards for human consumption. However, it can still be used for agricultural purposes, since the parameters analyzed are within the permitted limits.
Keywords: Colombia; pollution; governance; Index; water resources